Smes Development In Indonesia: Do Economic Growth And Government Support Matter? - Tambunan, Tulus (Penerbit Universiti Sains Malaysia (USM Press), 2008)
There is an ongoing debate in the literature on development of small and medium enterprises (SMEs) in less developed countries (LDCs) on two issues: The survival of SMEs in the course of economic development and the importance of government promotion programs for SMEs development. This research aims to examine those issues with Indonesian data. As a means to address those issues, it uses a simple regression model. It shows that both real gross domestic product (GDP) per capita and government development expenditure (in which part of it is used to finance SMEs development promotion programs) have positive correlations with SMEs share in GDP. With this finding, the research argues that SMEs in LDCs have a chance to survive and even to grow in the long-run for three main reasons: (a) they have a niche market for themselves; (b) these enterprises act as a 'last resort' for the poor; and (c) the production linkages between SMEs and large-enterprises (LEs) in the form of subcontracting have become increasingly important, and thus, they will grow along with the growth of LEs.